Pemantapan Sumber Daya Manusia (SDM) dalam Peningkatan Kesejahteraan Masyarakat Pengelola Sampah di Pasar Ciputat - Sutariyono Sutariyono; Adhy Firdaus; Devid Putra Arda; Muhammad Arief Noor; Fuad Siregar; M. Tafsiruddin; Cinta Rahmi; Haria Saputri; Moh Tahang; Aep Saefullah; Delima Indah Permatasari; Ibah Misbah (Jurnal Pengabdian Masyarakat Nusantara, 2020)
The human resource (HR) consolidation program in improving the welfare of the waste management community in Ciputat Market aims to improve the quality of life of waste managers through relevant training and education. Held during May 2021, this activity includes intensive training and counseling. Training includes waste management management, recycling techniques, and entrepreneurship, while counseling provides knowledge about the importance of environmental health and hygiene. Group discussions and field visits were also conducted to see best practices in waste management. The results of this activity show a significant increase in the skills and knowledge of waste managers, who are now able to apply recycling techniques more efficiently and utilize waste into products with selling value. Their awareness of the importance of maintaining environmental health and hygiene is also increasing, creating a cleaner and healthier market environment and increasing their income through the sale of recycled products. The implication of this activity is to improve the welfare of the waste management community in Ciputat Market. With the new skills they acquire, waste managers not only improve their own economic conditions but also contribute to the cleanliness and health of the market environment. This program shows that with the right training and education, waste managers can be effective agents of change in society.